1994
DOI: 10.1128/iai.62.2.606-614.1994
|View full text |Cite
|
Sign up to set email alerts
|

Excision of large DNA regions termed pathogenicity islands from tRNA-specific loci in the chromosome of an Escherichia coli wild-type pathogen

Abstract: Uropathogenic Escherichia coli 536 (06:K15:H31) carries two unstable DNA regions, which were shown to be responsible for virulence. These regions, on which the genes for hemolysin production (hly) and P-related fimbriae (prj) are located, are termed pathogenicity islands (PAI) I and II, and were mapped to positions 82 and 97, respectively, on the E. coli K-12 linkage map. Sequence analysis of the PAI region junction sites revealed sequences of the leuX and selC loci specific for leucine and selenocysteine tRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
176
0
3

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 394 publications
(184 citation statements)
references
References 48 publications
5
176
0
3
Order By: Relevance
“…Neither foc hly cnf1 strains or foc papG seP strains were associated with the spe-ci¢c serotypes. Recently, it has been shown that large segments of the chromosome called pathogenicity islands (PAIs) accommodate many virulence genes of uropathogenic E. coli [17,18]. It is unclear, however, that the associations among the virulence determining genes in our results re£ect such genetic linkage, functional association or epidemiological association.…”
Section: Discussionmentioning
confidence: 68%
“…Neither foc hly cnf1 strains or foc papG seP strains were associated with the spe-ci¢c serotypes. Recently, it has been shown that large segments of the chromosome called pathogenicity islands (PAIs) accommodate many virulence genes of uropathogenic E. coli [17,18]. It is unclear, however, that the associations among the virulence determining genes in our results re£ect such genetic linkage, functional association or epidemiological association.…”
Section: Discussionmentioning
confidence: 68%
“…In recent years, 'pathogenicity islands' (PAIs) have attracted a great deal of attention (Kaper and Hacker, 1999). First described in the genomes of pathogenic E. coli, they were subsequently also found in other pathogens, where they form specific entities associated with bacterial pathogenicity (Blum et al, 1994). Sequencing of several entire genomes revealed that PAIs are much more widespread than previously thought, and represent a paradigm of more general genetic entities that are present in the genomes of many bacterial species and are termed genomic islands (Strauss and Falkow, 1997;Hacker and Kaper, 2000).…”
Section: Genomic Islands: Elements Of the Flexible Gene Poolmentioning
confidence: 99%
“…Genomic DNA for the analysis by pulsed-field gel electrophoresis (PFGE) was prepared and cleaved as described by Blum et al [3]. Restriction enzyme SfI was obtained from Boehringer (Mannheim, Germany).…”
Section: Pulsed-field Gel Electrophoresis (Pfge)mentioning
confidence: 99%
“…The virulence associated genes, which may code for adhesins, toxins, capsules, invasines and other virulence factors, may be located on large plasmids, on genomes of bacteriophages or on the chromosome of the pathogenic strains [2]. Recently, we have described particular DNA units on the chromosome of the uropathogenic E. coli strain 536 which carry virulence associated genes coding for cY-hemolysin and P-fimbriae [3,4]. The regions have been termed 'pathogenicity islands' (Pais) [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation